Evaluation of Building Facilities Maintenance Practices in Public Tertiary Institutions in Abia State, Nigeria - Okechukwu, B. N.; Oladejo, E. I. (International Journal of Real Estate, 2025)
This study evaluates the state of building facilities maintenance in public tertiary institutions in Abia State, Nigeria, with emphasis on identifying current practices, user satisfaction, challenges, and strategies for improvement. A cross-sectional survey design was adopted, and data were collected from 1,101 respondents across Abia State University, Michael Okpara University of Agriculture Umudike, and Abia State Polytechnic Aba. Structured questionnaires, interviews, and observations were used, and results were analyzed using descriptive statistics, correlation analysis, and t-tests. Findings revealed that most facilities were either averagely maintained or in poor condition, with 71.9% of students expressing dissatisfaction and 81.5% reporting insufficiency of available facilities. Insufficient funding (83.1%), use of substandard materials (55.6%), and poor government attitude (41.9%) emerged as the most critical challenges. Preventive and corrective maintenance methods were perceived as the most effective approaches to sustaining academic performance. The study concludes that sustainable maintenance requires adequate funding, skilled personnel, application of standard materials, and consistent maintenance policies. It recommends that government and institutional authorities prioritize preventive strategies, allocate dedicated budgets, and adopt user-focused maintenance frameworks to improve the learning environment and enhance educational outcomes.